Synthesis of 8-Bromoflavone and Its Buchwald–Hartwig Reaction with Amines - Pajtás, Dávid; Patonay, Tamás; Kónya, Krisztina (Synthesis, 2016)
Simple and convenient synthesis of 8-bromoflavone was achieved, starting from 2-bromophenol through 3′-bromo-2′-hydroxyacetophenone whose preparation was managed to be solved by optimized Fries rearrangement. The Buchwald–Hartwig reaction of 8-bromoflavone with different type of primary and secondary amines was carried out.
Keywords: palladium; Buchwald–Hartwig reaction; flavones; catalysis; Fries rearrangement